Invasion of epithelial cells by Shigella flexneri induces tyrosine phosphorylation of cortactin by a pp60c-src-mediated signalling pathway. - Dehio, C (1995)
Shigella flexneri causes bacillary dysentery in humans by invading epithelial cells of the colon. Cell invasion occurs via bacterium-directed phagocytosis, a process requiring polymerization of actin at the site of bacterial entry. We show that invasion of HeLa cells by S.flexneri induces tyrosine phosphorylation of cortactin, a host cell protein previously identified as a cytoskeleton-associated protein tyrosine kinase (PTK) substrate for the proto-oncoprotein pp60c-src. Immunolocalization experiments indicate that cortactin is recruited to submembranous actin filaments formed during bacterial entry. In particular, cortactin is highly enriched in membrane ruffles of the entry structure, which engulf entering bacteria, and also in the periphery of the phagosome early after bacterial internalization. The proto-oncoprotein pp60c-src appears to mediate tyrosine phosphorylation of cortactin, since overexpression of this PTK in HeLa cells specifically increases the level of cortactin tyrosine phosphorylation induced during bacterial entry. Immunolocalization studies in pp60c-src-overexpressing HeLa cells indicate that pp60c-src is recruited to the entry structure and to the periphery of the phagosome, where pp60c-src appears to accumulate in association with the membrane. Our results suggest that epithelial cell invasion by S.flexneri involves recruitment and kinase activation of pp60c-src. Signalling by the proto-oncoprotein pp60c-src may play a role in cytoskeletal changes that facilitate S.flexneri uptake into epithelial cells, since transient overexpression of pp60c-src in HeLa cells can provoke membrane ruffling and appears also to stimulate bacterial uptake of a non-invasive S.flexneri strain.